Business Ethics in Australia and New Zealand - Milton-Smith, John (Journal of business ethics, 1997)
The scandals of the 1980s, extending into the 1990s, came as a profound shock to Australians and New Zealanders. Both countries have prided themselves – somewhat smugly and naively – on being open, fair and honest societies. So it was very disillusioning to see both corruption and gross dereliction of duty exposed in virtually every sphere of public life. Perhaps the most positive outcome, however, amidst an almost daily diet of amazing revelations, has been the ability of the ‘system’ – and especially the judiciary and the media – to expose and deal with corruption even at the highest level., Following an extensive survey and literature review, it is clear that there is now widespread awareness of the need for reform in many areas of public administration, corporate governance and professional behaviour. However, a continuing cause for concern is the lack of leadership in identifying and addressing complex ethical dilemmas, particularly in the areas of conflict of interest and disclosure., Feedback from professional bodies, industry associations and university business schools indicates slow but uneven progress in ethics education. While several ethic centres and prominent individual ethicists have introduced innovative programs and given ethical issues greater prominence in the media, narrow vocationalism still takes precedence over personal values in the business and management curriculum.